Comparison of macular retinal thickness measurements using spectral-domain and swept-source optical coherence tomography in healthy eyes - Wan, Huan; Wu, Zhaode; Liu, Ziling; Qin, Bo (Frontiers in Medicine, 2025)
AimThis study compares retinal thickness measurements in healthy eyes using one SD-OCT and two SS-OCT devices to assess differences and consistency for clinical application.MethodsForty-eight eyes with a mean age of 28.15 ± 8.85 years were enrolled. Retinal thickness was measured using Heidelberg Spectralis SD-OCT, Svision VG200 SS-OCT, and TowardPi En Face SS-OCT. Normally distributed data were presented as mean ± SD; non-normal data as median (P25–P75). Intraclass correlation coefficients (ICC) and Bland–Altman analysis were used to assess agreement, with a 7 μm error threshold.ResultsSignificant differences were found between the three devices (p < 0.001). SD-OCT measurements were consistently lower than SS-OCT (p < 0.001), while the two SS-OCT devices showed no significant differences except in the nasal region (p = 0.006). ICC values between SD-OCT and SS-OCT devices were low (0.125–0.532), while SS-OCT devices showed better agreement (ICC: 0.369–0.922). Bland–Altman analysis found only 8.33% of SD-OCT and SS-OCT measurements within the 7 μm error range, compared to 81.25–83.33% for SS-OCT devices.ConclusionThe measurements of macular retinal thickness using SD-OCT and SS-OCT devices showed poor consistency and cannot be used interchangeably. However, measurements obtained from different SS-OCT devices demonstrated good consistency. To enhance the accuracy of results, it is recommended to maintain consistency in the devices used for follow-up examinations in the same patient.